KARAKTERISTIK IDEAL SIKAP RELIGIUSITAS PADA MASA DEWASA - Iswati Iswati (AT-TAJDID, 2018)
The purpose of this paper is to examine how the ideal characteristics of religious attitudes in adulthood. Adulthood is a period where an individual has completed his growth both on physiological, psychological and sociological aspects. In adulthood, people already have responsibilities, have realized the meaning of life. already has a clear identity and a strong personality. The attitude of adult religiosity has a broad perspective based on the values chosen. This attitude is generally based on deepening the understanding and expansion of understanding of the teachings of the religion he adheres to. Stability in the view of religious life and the religious behavior of adult humans is dynamic stability. They understand the nature of their creation "I live and I know what for". However, in order to lead to religious maturity there are also some obstacles, those who are able to accept the ratio will appreciate and then practice the teachings of the religion well, on the contrary, people who are less able to accept the ratio will depend more on the existing community.